India - Nardo, Don, 1947- (New York : Children's Press, 2012)
An introduction to the geography, history, culture, and people of India.
Land of striking contrasts -- The great subcontinent -- Fantastic variety -- An "incredible drama" -- The world's largest democracy -- Building an economy -- A growing nation -- Many faiths -- Cultural crossroads -- Families, home, and school.
Includes bibliographical references and index.
Keywords: India -- Juvenile literature; India